2019
DOI: 10.1186/s12891-019-2646-5
|View full text |Cite
|
Sign up to set email alerts
|

The two-year incidence of hip osteoarthritis after arthroscopic hip surgery for femoroacetabular impingement syndrome

Abstract: Background One of the reported goals of hip preservation surgery is to prevent or delay the onset of osteoarthritis. This includes arthroscopic surgery to manage Femoroacetabular Impingement (FAI) Syndrome. The purpose of this study was to describe the prevalence of clinically-diagnosed hip OA within 2 years after hip arthroscopy for FAI syndrome, and 2) determine which variables predict a clinical diagnosis of OA after arthroscopy. Methods Observational analysis of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
0
20
1
1
Order By: Relevance
“…The present study did not find BMI, sex, or race to be predictive of conversion to THA within 2 years. Other studies have also shown that prior hip arthroscopy or surgeries have been associated with predictors of clinical outcomes, 14 , 31 whereas the present study did not note prior hip arthroscopy as a significant predictor of conversion, despite it being statistically significant. Additional factors previously associated with conversion have been worsening preoperative evidence of arthritic changes or chondral damage 20 , 22 , 23 , 25 , 26 , 28 , 33 , 34 , 35 or acetabular morphology.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…The present study did not find BMI, sex, or race to be predictive of conversion to THA within 2 years. Other studies have also shown that prior hip arthroscopy or surgeries have been associated with predictors of clinical outcomes, 14 , 31 whereas the present study did not note prior hip arthroscopy as a significant predictor of conversion, despite it being statistically significant. Additional factors previously associated with conversion have been worsening preoperative evidence of arthritic changes or chondral damage 20 , 22 , 23 , 25 , 26 , 28 , 33 , 34 , 35 or acetabular morphology.…”
Section: Discussioncontrasting
confidence: 89%
“…It is important to consider that prior studies have not used a consistent definition of osteoarthritis or “failure” of hip arthroscopy. The manner in which studies evaluate progression of disease and outcomes have included clinical diagnoses and electronic medical record coding, 14 patient-reported outcome measures, 6 , 12 , 13 , 24 imaging changes, 7 , 15 and subsequent hip arthroscopy or THA. 2 , 4 , 13 , 18 , 19 , 25 Because of the variability in defining outcomes, it is important to evaluate each study’s outcome measures carefully.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, many studies have focused on results of hip arthroscopy overall, including patient indications and complications. 32,33 Operative hip is in 0o flexion, 0o rotation (neutral position); (B) The C-arm is set to 0 tilt, À10 cantilever. Note: the patient is intentionally placed in Trendelenburg to minimize perineal pressure.…”
Section: Discussionmentioning
confidence: 99%